Pengaruh Pemberian Kompos Kulit Buah Kopi Terhadap Pertumbuhan Bibit Kopi Robusta (Coffea Canephora) - Riki Riswandi; Wulan Kumala Sari (Jurusan Budidaya Perkebunan, 2021)
Coffee is a estate commodity that plays an important role in the economy of Indonesian. Plant nursery with proper planting medium is one of the important cultivation efforts to produce optimal coffee production. The objectives of this research were to study the effect of coffee rind compost on the growth of robusta coffee (Coffea canephora) seedlings and to obtain the best dose of it on the growth of robusta coffee. This research was conducted for 4 months at the experimental field of 3rd Campus, Andalas University where located in Dharmasraya District at altitude of 131 m above sea level. Experiment was arranged according to a completely randomized design (CRD) consisted of 5 treatments and repeated 5 times, in order to obtain 25 experimental units, each of it contained 2 sample plants, so that there were 50 plants in total. The results showed that the application of coffee rind compost had a significant effect on the growth of robusta coffee (C. canephora) seedlings on the variables of plant height, stem diameter, number of leaves, leaf length, and leaf width. The best dose of coffee rind compost to support the growth of robusta coffee seedlings was 300 g / polybag.